Shadow Tax Phenomenon In Indonesian Tax Law: Analysis Of Non-State Levies In Residential Areas - Aulia Salma Istisofani (JURNAL MAHASISWA YUSTISI, 2026)
This study examines the phenomenon of shadow tax within the framework of Indonesian tax law, focusing on levies imposed by non-state entities in residential areas. The primary issue addressed is the legality of additional charges on clean water services that are unilaterally and coercively imposed by residential management bodies. Using a normative legal method combined with a case study approach, this research evaluates whether such practices comply with the principles and elements of taxation. The findings reveal that these levies substantively resemble taxes due to their mandatory nature, collective imposition, and recurring financial burden. However, they lack formal legitimacy because they are not based on statutory provisions as required under Article 23A of the 1945 Constitution of Indonesia. The layered cost structure (20%, 5%, and 5%) creates a double financial burden for residents and violates key principles of taxation, including legality, legal certainty, fairness, and utility. Therefore, such practices can be classified as shadow taxes, which harm the public and blur the boundaries between state authority and private actors in public revenue collection.